Bibliometric analysis on the applicability of anaerobic digestion in organic solid waste - Cavalcanti, Ingrid Lélis Ricarte; Leite, Valderi Duarte; de Oliveira, Roberto Alves [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2023)
Anaerobic biological treatment can comprise a viable route of CH4 production through the energy recovery of organic solid waste (OSW). This work therefore presented a bibliometric analysis of research trends on the theme Applicability of biological treatment via Anaerobic Digestion in Organic Solid Waste, considering experimental articles published from 2018 to 2022 in the Web of Science database™; the analysis used VoSviewer software to define research trends, and found that the main terms addressed in the mapped scientific articles were anaerobic, waste, sludge, waste food, municipal waste, anaerobic co-digestion, sewage sludge, organic fraction, co-digestion and biogas. As a product of such mapping, an Interaction Network Diagram was constructed comprising the main terms in addition to a theoretical foundation on anaerobic digestion and biochemical and microbiological aspects about the process.
Análise bibliométrica acerca da aplicabilidade da digestão anaeróbia em resíduos sólidos orgânicos
Keywords: anaerobic co-digestion; clean energy; food waste; microbial intercropping